Design of reflectarray antenna integrated with FSS textured configurations for wireless communication applications - Kiyani, Arslan (2014)
Modern communication systems require intelligent antenna arrays to achieve increased phase range for the performance improvement. Moreover the design requirements of spacecraft antennas for satellite communications and telecommunication missions require multifunction antennas to prevent the propagation of electromagnetic waves in certain frequency bands. This project investigates the feasibility of employing reflectarray antenna integrated with FSS textured configurations to combat the scan blindness problem. Performance investigation of different strategic resonant elements has been carried out in X-band frequency range by using commercially available computer models of CST MWS and Ansoft HFSS based on Finite Integral Method (FIM) and Finite Element Method (FEM) respectively. Frequency Selective characteristics are also exploited by embedding the dipole, square loop and triangular loop resonant elements on top of the groundless substrate. Integrated FSS Reflectarray (FSS-RA) configurations based on iterative loop length approach are than implemented for operation in both X and Ku-band to improve the static phase range for the reduction of phase errors resulting in scan blindness. It has been demonstrated that the maximum static phase range of 540° can be obtained with the loop length variation of 6.8mm. Moreover novel algorithms based on mathematical models have been developed for the calculation of progressive phase distribution depicted by each individual resonant element and resonant frequency estimation of FSS reflectarrays. In order to validate the authenticity of numerical results waveguide scattering parameter measurements have been carried out by fabricating two patch unit cells for each reflectarray resonant element. Measured results demonstrated that reduction in reflection area of resonant elements from 105.74mm2 to 7.33mm2 tends to increase the reflection loss values from 2.63dB to 20.25dB. Moreover, an increased measured static phase range of 290° offering the reduction in phase errors is also shown by employing the triangular loop element.